Pengembangan Media Powtoon dengan Model Discovery Learning untuk Meningkatkan Minat Belajar dan Hasil Belajar Siswa Kelas IV pada Pelajaran Pendidikan Pancasila - Maulidatul Khasanah; Liyana Sunanto (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
The primary objective of this study is to analyze the development, implementation, and impact of using Powtoon-based learning media integrated with the Discovery Learning model to enhance learning motivation and academic achievement among fourth-grade elementary students in Civics Education (PKN). This research adopts a Systematic Literature Review (SLR) approach guided by the PRISMA protocol, which includes stages of article identification, screening, inclusion, data extraction, and synthesis analysis. Literature was collected from reputable international and national databases, including Google Scholar, Elsevier, Springer, Taylor & Francis, Wiley, Emerald, and Sinta, covering publications between 2020 and 2025. An initial search yielded 1,078 articles, which were filtered based on inclusion and exclusion criteria to obtain 15 final journals for in-depth analysis. The findings reveal that integrating Powtoon media with the Discovery Learning model significantly enhances students’ learning motivation, engagement, and academic performance. Powtoon’s visual and animated features make learning more interactive and enjoyable, while Discovery Learning encourages exploration, problem-solving, and conceptual understanding. This combination fosters active participation, critical thinking, and deeper comprehension in PKN learning contexts. Most studies demonstrate that the use of Powtoon effectively increases students’ interest and learning outcomes across various subjects, especially when paired with inquiry-based strategies such as Discovery Learning. However, research focusing on the long-term implementation framework, teacher readiness, and evaluation models for Powtoon-based learning remains limited. Future research is recommended to develop more comprehensive and adaptive models that align with students’ learning needs and classroom realities. Keywords: Powtoon media, discovery learning, learning motivation, learning outcomes, Civics education, elementary school, systematic literature review.   Abstrak Tujuan utama penelitian ini adalah untuk menganalisis pengembangan, penerapan, dan pengaruh penggunaan media pembelajaran Powtoon yang terintegrasi dengan model Discovery Learning dalam meningkatkan minat dan hasil belajar siswa kelas IV pada mata pelajaran Pendidikan Kewarganegaraan (PKN). Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) dengan mengacu pada protokol PRISMA, melalui tahapan identifikasi artikel, penyaringan, inklusi, ekstraksi data, hingga analisis sintesis secara menyeluruh. Literatur dikumpulkan dari berbagai basis data nasional dan internasional, seperti Google Scholar, Elsevier, Springer, Taylor & Francis, Wiley, Emerald, dan Sinta, dengan periode publikasi antara tahun 2020 hingga 2025. Dari hasil pencarian awal sebanyak 1.078 artikel, dilakukan proses seleksi berdasarkan kriteria inklusi dan eksklusi, sehingga diperoleh 15 jurnal final yang dianalisis secara mendalam. Hasil penelitian menunjukkan bahwa penggunaan media Powtoon dengan model Discovery Learning memberikan pengaruh positif yang signifikan terhadap peningkatan minat belajar, keterlibatan siswa, serta hasil belajar akademik. Media Powtoon terbukti mampu menyajikan pembelajaran yang interaktif, menarik, dan visual, sehingga memudahkan pemahaman konsep dan mendorong partisipasi aktif siswa. Sementara itu, model Discovery Learning menumbuhkan rasa ingin tahu, kemampuan berpikir kritis, serta kemandirian belajar melalui proses penemuan dan eksplorasi. Kombinasi keduanya menciptakan pembelajaran PKN yang lebih kontekstual dan bermakna. Penelitian yang menyoroti pengembangan kerangka implementasi jangka panjang, kesiapan guru, serta evaluasi model pembelajaran Powtoon berbasis Discovery Learning masih terbatas. Oleh karena itu, diperlukan penelitian lanjutan yang mengembangkan model pembelajaran yang lebih komprehensif, adaptif, dan sesuai dengan kebutuhan peserta didik serta konteks sekolah dasar. Kata kunci: media Powtoon, discovery learning, sekolah dasar, minat belajar, hasil belajar, Pendidikan Kewarganegaraan, systematic literature review.